School Engagement Measure Instrument Adaptation - Masyitha Nur Ramadhani; Urip Purwono (Publikasi Indonesia, 2023)
School engagement is a multidimensional construct that refers to student involvement in schools in three dimensions, namely involvement in behavioral, emotional and cognitive aspects. School Engagement Measure is an instrument to measure student engagement in schools that has been widely used in various countries. In order to use the instrument in a culturally different way, an adaptation process is needed so that the adapted instrument is valid and reliable. The purpose of this study was to obtain a standardized version of the School Engagement Measure in Indonesia. The International Test Commission Guidelines (2017) were used in the adaptation process. Based on the results of the CFA analysis using the JASP 0.15.0.0 program, it can be concluded that the overall School Engagement Measure model with indicators consisting of three dimensions, namely behavioral engagement, Emotional engagement and cognitive engagement, has a good fit model. The null hypothesis means that the SEM model is acceptable. This explains that the resulting model can describe the actual conditions.